Rancang Bangun Aplikasi E-Commerce Upscale Building pada CV. Upscale Team Berbasis Website - Andrew Nofa Ardyanti (Journal Of Informatics And Busisnes, 2025)
E-commerce is the process of buying, selling and marketing goods and services via the internet. Consumers can buy products, services and anything else online. CV. Upscale Team is a company that operates in the field of building design and construction services. The service process provided by CV. The Upscale Team is still offline and is experiencing problems from clients who are having difficulty monitoring design progress and building construction work stages because progress is currently being explained via chat or telephone which results in less detailed information being received by clients. CV. Upscale Team needs a solution, namely building a web-based e-commerce marketing design and development service that can make it easier for clients to consult and monitor development progress. The method used in this research is the Rapid Application Development (RAD) method to create web-based e-commerce using Blackbox Testing with the results of the system display, system functions and system flow from the user and admin point of view. The results show that the system can run well. This shows that the e-commerce marketing system at CV. Upscale Team can increase effectiveness and efficiency in service delivery.